Conservation of Freshwater Fish Biodiversity: A Challenge for Rajasthan (International Journal of Scientific Research and Management (IJSRM), 2017)
Fish biodiversity is associated with deserts around the globe. Freshwater fishes have suffered from the resultant altered flow regime, together with other threats including habitat degradation and alien species. Impacts reached a critical point during prolonged droughts that lead to broad-scale habitat loss and drying of refuges during, and urgent conservation measures were subsequently instigated for threatened small-bodied fish species. The present paper aims to document the actions undertaken in the desert hatchery of Western Rajasthan by induced breeding exercises on common carp, rohu and mrigal using ovaprim hormone that will help guide and inform management responses for conservation of threatened fishes in modified systems subjected to severe water decline